Travel Website Development Project Management Using The Agile Scrum Method - Endra Rahmawati; Muhammad Zerq Elvonda Graha Yuda; Sri Hariani Eko Wulandari (Journal of Engineering, Electrical and Informatics, 2025)
PT. Lentera Bangsa Benderang, which houses Binar Academy, is an educational institution that contributes to technology development in Indonesia. The company actively supports the development of digital-based technology, including a project to develop an airline ticket purchasing website for a travel client called GarudaNih. However, the company has a history of project delays of 40%. These delays occur due to a lack of backlog management, poorly managed changes in client needs, and ineffective communication between teams. Therefore, research was conducted to address the problem by offering the Agile Scrum method. In this study, effective and iterative stages were formulated in accordance with the methodology to resolve project issues on time. Furthermore, the feasibility of the method was tested as a solution to the disruption experienced by the project using Burndown Charts, Velocity, and Cycle Time. This research resulted in the application of the method to project management as an effort to overcome various problems previously faced by Binar Academy. Furthermore, the results of this study also proved that the method used had been tested for its feasibility and could be an effective solution in overcoming existing obstacles.